Transcriptome and Metabolite Profiling of the Infection Cycle of Zymoseptoria tritici on Wheat Reveals a Biphasic Interaction with Plant Immunity Involving Differential Pathogen Chromosomal Contributions and a Variation on the Hemibiotrophic Lifestyle Definition. Issue 3 (16th January 2015) - Rudd, Jason J.; Kanyuka, Kostya; Hassani-Pak, Keywan; Derbyshire, Mark; Andongabo, Ambrose; Devonshire, Jean; Lysenko, Artem; Saqi, Mansoor; Desai, Nalini M.; Powers, Stephen J.; Hooper, Juliet; Ambroso, Linda; et al.
Abstract : The temporal dynamics of Zymoseptoria tritici reproduction on Triticum aestivum involves a biphasic manipulation of plant defense responses. Abstract: The hemibiotrophic fungus Zymoseptoria tritici causes Septoria tritici blotch disease of wheat ( Triticum aestivum ). Pathogen reproduction on wheat occurs without cell penetration, suggesting that dynamic and intimate intercellular communication occurs between fungus and plant throughout the disease cycle. We used deep RNA sequencing and metabolomics to investigate the physiology of plant and pathogen throughout an asexual reproductive cycle of Z. tritici on wheat leaves. Over 3, 000 pathogen genes, more than 7, 000 wheat genes, and more than 300 metabolites were differentially regulated. Intriguingly, individual fungal chromosomes contributed unequally to the overall gene expression changes. Early transcriptional down-regulation of putative host defense genes was detected in inoculated leaves. There was little evidence for fungal nutrient acquisition from the plant throughout symptomless colonization by Z. tritici, which may instead be utilizing lipid and fatty acid stores for growth. However, the fungus then subsequently manipulated specific plant carbohydrates, including fructan metabolites, during the switch to necrotrophic growth and reproduction. This switch coincided with increased expression of jasmonic acid biosynthesis genes and large-scale activation of other plant defense responses. Fungal genes encoding putative secondary metabolite clusters and secreted effector proteins were identified with distinct infection phase-specific expression patterns, although functional analysis suggested that many have overlapping/redundant functions in virulence. The pathogenic lifestyle of Z. tritici on wheat revealed through this study, involving initial defense suppression by a slow-growing extracellular and nutritionally limited pathogen followed by defense (hyper) activation during reproduction, reveals a subtle modification of the conceptual definition of hemibiotrophic plant infection.